Study of Cyclic Variability in Diesel-Hydrogen Dual Fuel Engine Combustion - Widodo Budi, Santoso; R. A., Bakar; Sugeng, Ariyono; Nur, Cholis (IJENS, 2012)
Among the alternative fuels, hydrogen shows great potential in the near future. In the present study, the cyclic variability of a diesel engine fueled with hydrogen and ignited by diesel spray was studied. To investigate the combustion characteristics of this dual fuel engine, a single cylinder diesel research engine was converted to utilize hydrogen as fuel. Hydrogen was introduced to the intake manifold using a mixer before entering the combustion chamber. The engine was run at a constant speed of 2000 rpm and variable loads. At each load step the flow rate of hydrogen was varied. An engine indicating system was used to measure and record the cylinder pressure up to 160 consecutive combustion cycles. The combustion data for each operating conditions were analyzed for the maximum cylinder pressure and indicated mean effective pressure (IMEP). The cycle-by-cycle variation is expressed as the mean value, standard deviation, coefficient of variation of these two parameters. It is found that cyclic variability is reduced at higher engine load operation.